Gross and Micro Anatomical Study of Placenta from Normal and Hypertensive Pregnancies - Mishal, Jyoti; Jha, Chandra Bhushan; Shrestha, Shailaja Chhetri; Agrawal, Yamuna; Chaudhary, Archana; Maharjan, Nikky (Nepal Journal of Health Sciences, 2022)
Introduction: The examination of the placenta gives a clear idea of what happened with fetus when it was in the mother’s womb. The changes in placenta of women with pregnancy induced hypertension and normal pregnancies can be compared. Objective: This study was done to find out differences in gross structure and histology between normal and hypertensive placentas. Methods: Placenta from case and control group was collected from the Gynecology and Obstetrics Department of B.P.Koirala Institute of Health Sciences, Dharan. The histology slides were prepared, examined and parameters was collected. Results: The mean weight of placenta in control group was 469.5±148.9gm and in case group was 375.50 ± 109.08gm which was statistically significant. The histological observation of syncytial knot, hyalinized villi, stromal fibrosis, necrosis, hemorrhage and calcification in placenta was significantly higher in case group than that of in normotensive group. Conclusions: It is concluded that, in hypertension complicating pregnancy, with increase of severity, there is decrease in morphology and increase in abnormal histological changes of placenta. So, the reduction in placental morphological parameters and histological changes might be the reason for retarded growth of baby with increased complication of hypertension.